Lucky day - Tingle, Chuck (Nightfire, Tor Publishing Group, 2025)
""An existential masterwork that, like life, is equal parts atrocity and delights."-Olivie Blake, New York Times bestselling author of Masters of Death. Lucky Day is the latest from Chuck Tingle, USA Today bestselling author of Camp Damascus and Bury Your Gays, where one woman must go up against horrifying odds to save the world. Four years ago, an unthinkable disaster occurred. In what was later known as the Low-Probability Event, 8 million people were killed in a single day, each of them dying in improbable, bizarre ways: strangled by balloon ropes, torn apart by exploding manhole covers, attacked by a chimpanzee wielding a typewriter. A day of freak accidents that proved anything is possible, no matter the odds. Luck is real now, and it's not always good. Vera, a former statistics and probability professor, lost everything that day, and she still struggles to make sense of the unbelievable catastrophe. To her, the LPE proved that the God of Order is dead and nothing matters anymore. When Special Agent Layne shows up on Vera's doorstep, she learns he's investigating a suspiciously-and statistically impossible-lucky casino. He needs her help to prove the casino's success is connected to the deaths of millions, and it's Vera's last chance to make sense of a world that doesn't. Because what's happening in Vegas isn't staying there, and she's the only thing that stands between the world and another deadly improbability... Also by Chuck Tingle: Bury Your Gays, Camp Damascus, Straight."--